Analysis of the anti-apoptotic protein bcl-2 in oral squamous cell carcinoma - Popović Branka; Jekić Biljana; Novaković Ivana; Milašin Jelena (Serbian Medical Society - Dental Section, Belgrade, 2007)
Aim: The aim of this study was to analyze the presence of the anti-apoptotic protein bcl-2 in oral squamous cell carcinoma and determine its potential role in the development and progression of this type of tumor. Materials and methods: The expression of bcl-2 was determined in 28 paraffin blocks of oral squamous cell carcinoma using the immunohistochemical method. The percentage of the immuno-reactive cells in positively stained tumor regions was determined using the microscopic analysis and Ozaria software. Results: Positive immunohistochemical test was observed in 19 out of 28 samples (68%) as follows: in 11 samples there was a low (+), in four a moderate (++) and in the last four a high percentage (+++) of stained cells. In the group of patients at the low stage of the disease (T2), 50% of tumor samples showed bcl-2 protein expression whereas in the higher stages (T3 and T4) of positively stained samples, this percentage was 67%. There was a trend of an increasing number of cells with positive bcl-2 staining in the tumors of higher clinical stages but not the level of bcl-2 protein expression. Conclusion: Both parameters, the presence of bcl-2 staining and the percentage of cells with bcl-2 immunoexpression, may act as additional prognostic parameters that indicate an increased proliferative tumor potential.